Oxidative stress and antioxidant status in primary bone and soft tissue sarcoma - Nathan, F.M.; Singh, V.A.; Dhanoa, A.; Palanisamy, U.D. (BioMed Central, 2011)
Background: Oxidative stress is characterised by an increased level of reactive oxygen species (ROS) that disrupts the intracellular reduction-oxidation (redox) balance and has been implicated in various diseases including cancer. Malignant tumors of connective tissue or sarcomas account for approximately 1 of all cancer diagnoses in adults and around 15 of paediatric malignancies per annum. There exists no information on the alterations of oxidant/antioxidant status of sarcoma patients in literature. This study was aimed to determine the levels of oxidative stress and antioxidant defence in patients with primary bone and soft tissue sarcoma and to investigate if there exists any significant differences in these levels between both the sarcomas. Methods: The study cohort consisted of 94 subjects; 20 soft tissue sarcoma, 27 primary bone sarcoma and 47 healthy controls. Malondialdehyde (MDA) and protein carbonyls were determined to assess their oxidative stress levels while antioxidant status was evaluated using catalase (CAT), superoxide dismutase (SOD), thiols and trolox equivalent antioxidant capacity (TEAC). Results: Sarcoma patients showed significant increase in plasma and urinary MDA and serum protein carbonyl levels (p < 0.05) while significant decreases were noted in TEAC, thiols, CAT and SOD levels (p < 0.05). No significant difference in oxidative damage was noted between both the sarcomas (p > 0.05). Conclusions: In conclusion, an increase in oxidative stress and decrease in antioxidant status is observed in both primary bone and soft tissue sarcomas with a similar extent of damage. This study offers the basis for further work on whether the manipulation of redox balance in patients with sarcoma represents a useful approach in the design of future therapies for bone disease.